2020
DOI: 10.1038/s41598-020-59999-w
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule activation of metabolic enzyme pyruvate kinase muscle isozyme 2, PKM2, circumvents photoreceptor apoptosis

Abstract: Photoreceptor cell death is the ultimate cause of vision loss in many retinal disorders, and there is an unmet need for neuroprotective modalities to improve photoreceptor survival. Similar to cancer cells, photoreceptors maintain pyruvate kinase muscle isoform 2 (PKM2) expression, which is a critical regulator in aerobic glycolysis. Unlike PKM1, which has constitutively high catalytic activity, PKM2 is under complex regulation. Recently, we demonstrated that genetically reprogramming photoreceptor metabolism … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 57 publications
5
47
0
Order By: Relevance
“…Mohammad et al [ 232 ] found that the use of TEPP-46 significantly enhanced PK activity in pancreatic cancer cells, downregulated PKM2 dimer expression, and inhibited the growth of tumors in a mouse model. In addition, many molecules, such as parthenolide (PTL 5) ( Figure 6 I) [ 233 ], ML-265 ( Figure 6 K) [ 234 ], PA-12 [ 235 ], Pyridin-3 ylmethyl carbamodithioic esters [ 236 ], ZINC08383544 [ 237 ], and compound 0089-0022 [ 238 ], inhibit tumor growth as PKM2 agonists. Some researchers have also explored the effects of herbal components on PKM2 enzyme activity.…”
Section: Drugs That Target Glucose Metabolism Enzymesmentioning
confidence: 99%
“…Mohammad et al [ 232 ] found that the use of TEPP-46 significantly enhanced PK activity in pancreatic cancer cells, downregulated PKM2 dimer expression, and inhibited the growth of tumors in a mouse model. In addition, many molecules, such as parthenolide (PTL 5) ( Figure 6 I) [ 233 ], ML-265 ( Figure 6 K) [ 234 ], PA-12 [ 235 ], Pyridin-3 ylmethyl carbamodithioic esters [ 236 ], ZINC08383544 [ 237 ], and compound 0089-0022 [ 238 ], inhibit tumor growth as PKM2 agonists. Some researchers have also explored the effects of herbal components on PKM2 enzyme activity.…”
Section: Drugs That Target Glucose Metabolism Enzymesmentioning
confidence: 99%
“…Here we show that RTBDN ablation can affect the rate of glycolysis in a similar manner as Pkm2 −/− , but promoting PPP to meet the enhanced need of free-radical scavenging only serves as a short-term coping mechanism, and soon degeneration ensues. This strategy seems partially similar to therapeutic approaches suggested for acute stress conditions (20,38). An important feature of our research is that it determined the factors that precede, and may lead to, functional decline and eventual degeneration, providing critical insights into the primary causes behind retinal degeneration.…”
Section: Neurosciencementioning
confidence: 76%
“…It is well-established that the less active PKM2 dimer drives aerobic glycolysis, whereas the active PKM2 tetramer produces pyruvate for oxidative phosphorylation ( Christofk et al, 2008 ; Hitosugi et al, 2009 ; Anastasiou et al, 2012 ). The mechanisms involved in the PKM2 dimer-tetramer dynamics include fructose-1,6-biphosphate-mediated PKM2 tetramerization ( Dombrauckas et al, 2005 ), tyrosine phosphorylation ( Yang, 2015 ), acetylation ( Prakasam et al, 2018 ), and modulation by small molecule PKM2 activators ( Wubben et al, 2020 ). In the present study, we identified DPYSL2 as a novel regulator that promotes the conversion of PKM2 tetramers to dimers.…”
Section: Discussionmentioning
confidence: 99%